2001
DOI: 10.1103/physrevlett.86.5231
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions for Flat Anti–de Sitter Black Holes

Abstract: We reexamine the thermodynamics of anti-de Sitter (adS) black holes with Ricci flat horizons using the adS soliton as the thermal background. We find that there is a phase transition which is dependent not only on the temperature but also on the black hole area, which is an independent parameter. As in the spherical adS black hole, this phase transition is related via the adS/conformal-field-theory correspondence to a confinement-deconfinement transition in the large- N gauge theory on the conformal boundary a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(164 citation statements)
references
References 21 publications
(23 reference statements)
9
155
0
Order By: Relevance
“…This phase transition was interpreted as a confinement/deconfinement transition in the associated large N gauge theory on the boundary [40]. Taking a cue from this, it was shown that a phase transition also occurs between the toroidal black hole and the AdS soliton, and can also be interpreted as a confinement/deconfinement transition in the boundary field theory, in much the same way [37]. Indeed the choice of ground state is crucial to see such a phase transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phase transition was interpreted as a confinement/deconfinement transition in the associated large N gauge theory on the boundary [40]. Taking a cue from this, it was shown that a phase transition also occurs between the toroidal black hole and the AdS soliton, and can also be interpreted as a confinement/deconfinement transition in the boundary field theory, in much the same way [37]. Indeed the choice of ground state is crucial to see such a phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of this conjecture is thus an important test of the nonsupersymmetric version of the AdS/CFT correspondence. 4 A preliminary indication that the soliton is the appropriate ground state comes from a semi-classical thermodynamic analysis of Ricci flat black holes in the background of the AdS soliton [37]. An examination of the thermodynamics of the spherical AdS black hole showed that there is a phase transition that takes place between the black hole and the appropriate ground state, namely AdS spacetime [22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus the structure at infinity for the AdS instanton is precisely a compact, flat, ndimensional manifold. The very fact that the instanton is a well-behaved, unique ground state [74][75] [76] for these black holes strongly suggests that vanishing scalar curvature on the boundary is compatible with a stable field theory there, dual to one of these physically well-defined bulk configurations. Thus, we do have a large class of examples in which zero scalar curvature at the boundary is not pathological.…”
Section: Flatness Holography and Seiberg-witten Instabilitymentioning
confidence: 99%
“…(45) seems to tell that there is no phase transition when k = 0 or k = −2, which is not always true. There is an argument that it is easier to subtract the action of AdS soliton [24] instead of the vacuum AdS [25]. In this case, besides the temperature, the area of the horizon becomes an independent parameter on which the thermodynamical quantities depend.…”
Section: C-function From Ads Black Hole: No Deformationmentioning
confidence: 99%